2015
DOI: 10.1038/cddis.2015.370
|View full text |Cite
|
Sign up to set email alerts
|

C2238/αANP modulates apolipoprotein E through Egr-1/miR199a in vascular smooth muscle cells in vitro

Abstract: Subjects carrying the T2238C ANP gene variant have a higher risk to suffer a stroke or myocardial infarction. The mechanisms through which T2238C/αANP exerts detrimental vascular effects need to be fully clarified. In the present work we aimed at exploring the impact of C2238/αANP (mutant form) on atherosclerosis-related pathways. As a first step, an atherosclerosis gene expression macroarray analysis was performed in vascular smooth muscle cells (VSMCs) exposed to either T2238/αANP (wild type) or C2238/αANP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Our group demonstrated that the T2238C variant of the atrial natriuretic peptide (ANP) gene, a nonmodifiable risk factor for cardiovascular diseases including stroke, modulates ApoE level through miR-199 in vitro. The miR-199 up-regulation induced by C2238/αANP, and not by the wild type ANP, produced a downregulation of ApoE associated with decreased cell viability and increased apoptosis, necrosis, and inflammation in human vascular smooth muscle cells [96]. These results support the growing importance of miRNAs in the pathogenesis of stroke.…”
Section: Rna-based Mechanisms In Issupporting
confidence: 58%
“…Our group demonstrated that the T2238C variant of the atrial natriuretic peptide (ANP) gene, a nonmodifiable risk factor for cardiovascular diseases including stroke, modulates ApoE level through miR-199 in vitro. The miR-199 up-regulation induced by C2238/αANP, and not by the wild type ANP, produced a downregulation of ApoE associated with decreased cell viability and increased apoptosis, necrosis, and inflammation in human vascular smooth muscle cells [96]. These results support the growing importance of miRNAs in the pathogenesis of stroke.…”
Section: Rna-based Mechanisms In Issupporting
confidence: 58%
“…Human subjects carrying the T2238C ANP gene variant have a higher risk to suffer a stroke or myocardial infarction. C2238/␣ANP modulates apoE through Egr-1/miR199a in vascular smooth muscle cells in vitro (52). It will be interesting to investigate whether Egr-1 regulates A␤ clearance via apoE in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…23 Interestingly, ANP-RR reduced apolipoprotein E (ApoE) gene expression via NPR-C in VSMCs, which suggests NPR-C stimulation by ANP-RR interferes with the vasoprotective actions of ApoE. 24 These findings suggest that the rs5065 minor allele may produce a "malignant" ANP for the endothelium leading to atherosclerotic diseases through a NPR-C pathway. Therefore NPR-C inhibition may be a seminal therapeutic target for subjects with rs5065 to attenuate the risk of atherosclerotic diseases.…”
Section: Physiology Of Anpmentioning
confidence: 98%
“…Some reports suggest that NPR-C has roles in the L-type Ca 2+ current in myocytes and sino-arterial nodes together, 53 and to inhibit proliferation of cardiac fibroblasts with BNP. 54 On the other hand, it may be strategic to inhibit NPR-C because ANP-RR may mediate vascular injury via NPR-C; 24 as we stated before, because NPR-C seems to exhibit "pleiotropic" studies have been done because of the high cost and difficulties associated with large peptide synthesis for clinical use.…”
Section: Inhibition Of Anp Degradationmentioning
confidence: 99%